Roles of teachers in promoting oral health in schools: a cross sectional survey in Ibadan, Nigeria (2015)
The paucity of formal oral health promoting activities in schools in sub-Saharan Africa has not been properly addressed partly because of failure to integrate teachers with their roles. The study aimed to determine the roles of elementary school teachers in promoting oral health in schools in Ibadan, Nigeria. A questionnaire-based study was conducted among a representative sample of 338 teachers randomly selected from elementary schools in Ibadan. The majority, 308 (91.1%), believed that teachers should play important roles in promoting oral health in schools. Tooth cleaning by 272 (80.5%) and inspection of their pupils’ mouths by 206 (60.9%) teachers were the only oral health promotion activities the teachers were engaged in. Many, 258 (76.3%), were satisfied with their roles in promoting oral health in their schools while 29.0% were satisfied with the roles of dentists. Main reason mentioned by teachers for inadequate oral health promotion in schools was “dentists not doing enough” by 200 (59.2%) while the most commonly suggested solution to improve the situation was frequent school visitation by dentists, 261 (77.2%). Most, 297 (87.9%) were willing to be involved if oral health promoting activities are formally instituted. Many of the teachers believed they play important roles in promoting oral health in schools and are satisfied with their present activities in achieving this, despite very few oral health promotional activities existing in schools. Nonexistence of formal school oral health promotion activities were believed to be caused, majorly, by dentists not doing enough in schools.